2018
DOI: 10.1002/jcp.27505
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia with complex karyotypes: Prognosis and therapeutic approaches

Abstract: Objective and Background: Chronic myeloid leukemia (CML) is a neoplastic disease whose genetic and cytogenetic changes play important roles in prognosis and treatment strategies. Philadelphia (Ph) translocation t(9;22)(q34;q11) is a diagnostic and prognostic biomarker in CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Although the starting point of CML is well known, other genetic and cytogenetic changes play important roles in prognosis and treatment of this malignancy [79]. In this context, the mechanisms for insensitivity of CML stem remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the starting point of CML is well known, other genetic and cytogenetic changes play important roles in prognosis and treatment of this malignancy [79]. In this context, the mechanisms for insensitivity of CML stem remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CML, defined as a clonal myeloproliferative disorder, was the first human malignancy associated to a consistent chromosomal abnormality and is characterized by the presence of the fusion oncogene BCR-ABL. Clinical symptoms associated to this disease include hypercellular bone marrow, anemia, platelet dysfunction, and an increase in the number of leukocytes, especially neutrophils and immature myeloid cells [5, 6]. Chronic lymphocytic leukemia (CLL): it is more common in people over 60 years and is very rare in people under 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, −7, −17, +17, +21, -Y, and t(3;21)(q26;q22) were generated via the "minor" pathway, while about 15% of CML cases had at least one of these six chromosomal abnormalities [11]. Asnafi et al reviewed the additional chromosomal abnormalities discovered in CML-BC cases between 1975 and 2017 [9] and suggested that some chromosomal abnormalities are associated with poor prognosis and poor therapeutic responses to TKIs [9]. However, the impact of these additional chromosomal abnormalities on the development of a blast crisis remains unknown and detailed investigation will be required in the future.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although allogeneic hematopoietic stem cell transplantation is the only curative therapeutic option for CML-BC, the clinical outcome remains poor due to high rates of relapse and treatment-related mortality [8]. The pathogenesis of CML-BC remains unclear; however, additional chromosomal abnormalities may contribute to the progression of CML-BC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly, 10%‐12% of CML patients show additional chromosomal aberrations (ACAs) in chronic phase and blast crisis. ACAs, especially when complex, present to be a biomarker of CML evolution,and ACAs can be a important clue in treatment strategies . Rarely, patients with CML can present directly in a blast crisis.…”
Section: Introductionmentioning
confidence: 99%